On the irreconcilability of Pareto and Gibrat laws - Giulio Bottazzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
If business firms face a multiplicative growth process in which their growth rates are independent from their sizes, then these sizes cannot be distributed according to a stationary Pareto distribution. At the same time , the Laplace distribution of growth rates cannot be easily reconciled with a Pareto distribution of firm sizes. Recent contributions, using formal arguments, seems to contrast these statements. We prove that the proposed formal results are wrong.
Keywords: 330; Firm Growth; Gibrat's Law; Power law distribution; Laplace distribution; Betriebsgröße; Unternehmenswachstum; Betriebsgrößenstruktur; Statistische Verteilung; Theorie